THE RELATIONSHIP BETWEEN RELIGIUSITY AND CONFORMITY WITH MORAL INTEGRITY IN ELECTION MANAGERS IN DEMAK REGENCY - Mukorobin, Nailul; Suharsono, M; Susetyo, Daniel Purwoko Budi (UNISSULA, 2022)
The purpose of this research to test empirically the relationship between religiosity and conformity with moral integrity in election organizers in Demak district. The hypothesis put forward is there is positive relationship between religiosity and moral integrity in election organizers in Demak Regency. The research subjects amounted to 240 election organizers of Demak Regency. This study uses a quantitative method with documentation measuring instrument Religiosity Scale, Conformity Scale, and Moral Integrity Scale. The data obtained were then analyzed with multiple linear correlations. Based on the results of the analysis obtained value R=34,761and t = 10.962 with a p of 0.000 (p <0.01). Correlation coefficient value between Religiosity with Moral Integrity of Election Organizers in Demak Regency of 0.232 with a value of p: 0.000 (p <0.01) and the value of the correlation coefficient between conformity with the moral integrity of the election organizers in Demak Regency of 0.055 with a p-value: 0.393 (p>0.01). This means that there is a very significant positive relationship between religiosity and the moral integrity of election administrators in Demak Regency, and there is no relationship between conformity and the moral integrity of election organizers in Demak Regency.